2022
DOI: 10.21511/im.18(1).2022.15
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of purchase intention during COVID-19: A case study of skincare products in East Java

Abstract: During COVID-19, consumers of skincare products pay more attention to safety and comfort. In such a crisis, consumers seek skincare products with brand effectiveness, high quality, and persuasive reviews by social media influencers. This study investigates the influence of brand effectiveness, product quality, and celebrity endorsers on purchase intention of halal skincare products in the pandemic. The study employed a survey of halal skincare users in East Java, Indonesia. A purposive sampling of 180 female r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 55 publications
(17 reference statements)
0
15
0
1
Order By: Relevance
“…P1-High religious practices promote the purchase of non-alcoholic beverages by Christian consumers in the socio-cultural context of Burkina Faso. Sudaryanto, Courvisanos, and Rosediana (2022) have demonstrated the link between Muslim religious standards and consumer behavior. In addition,) Nasse et al (2019) have shown that the determinants for beverage consumption in the context are : nature of the beverage, friendship, purchasing power, pleasure and thirstiness.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…P1-High religious practices promote the purchase of non-alcoholic beverages by Christian consumers in the socio-cultural context of Burkina Faso. Sudaryanto, Courvisanos, and Rosediana (2022) have demonstrated the link between Muslim religious standards and consumer behavior. In addition,) Nasse et al (2019) have shown that the determinants for beverage consumption in the context are : nature of the beverage, friendship, purchasing power, pleasure and thirstiness.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Those closer to dimension 2, interpretable as "Effectiveness and Persuasiveness" (Brand, Quantity and Product Description); the relevance of this cluster is supported by [82];…”
Section: Distribution Of Categories Through Multiple Correspondence A...mentioning
confidence: 89%
“…The group of categories closer to dimension 1, interpretable as "Convenience" (Quality Information and Price); the relevance of this cluster is supported by [81]; 2. Those closer to dimension 2, interpretable as "Effectiveness and Persuasiveness" (Brand, Quantity and Product Description); the relevance of this cluster is supported by [82]; 3. Those at the interaction between the two dimensions, interpretable as "Sustainability and Responsibility" (Sustainability-Related Indications, Sustainability-Related Qual- In the analysis of form-related categories, three clusters could also be identified:…”
Section: Distribution Of Categories Through Multiple Correspondence A...mentioning
confidence: 92%
“…According to data from Juniman (2018), there are 48 companies with a total of 5,254 halal cosmetic products and in 2017 there were 64 companies with a total of 3,219 products and in March 2018 there were 41 companies with a total of 2,115 products with Halal certification. According to Sudaryanto et al, (2022), the large Muslim population in Indonesia is one of the reasons why halal-branded skin care products were launched in Indonesia in 2018. Islam, as the fastest growing religion in the world that promotes cleanliness and high product quality, Halal-certified skin care products have broader market appeal among non-Muslim consumers who may attribute these products to more stringent ethical consumerism and quality assurance standards (Ngah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%